Selection of a Combined Heat and Power (CHP), and CHP Generation Compared to Buying of Electrical Power from the National Grid and Separate Thermal Heat Production - Apunda, Moses Otieno; Nyangoye, Benard Oloo (Open Science Journal, 2017)
In this work, Combined Heat and Power (CHP) is critically discussed and its application analytically compared with alternative energy source.CHP efficiency was first compared with the conventional generation and realised that, for equivalent heat and power production, CHP exhibits a higher efficiency than conventional generation. For example, energy input of 215J and 170J for Conventional generation and CHP respectively produces equal amounts of heat and power with CHP having efficiency of 76.5% which is 16.5% more efficient than the conventional type with 60%. Factors influencing the choice of a CHP plant such as financial considerations, Environmental and Compliance considerations, Site Specific considerations and Technical parameters Considerations are vastly discussed. Since the choice of a CHP and its application depends on the type of the prime mover, different types of the CHPs and their applications were then discussed to understand their working principles and the choice of the fuel used. Two typical case scenarios were analytically compared to look into the most economical way of acquiring heat and power for a plant. Cogeneration (A) was compared with buying of electrical power from the national grid and at the same time producing thermal energy in the plant using natural gas fired boiler(B). From cost analysis of the case scenarios, it is confirmed that cogeneration (A) is the most economical aspect compared to alternative B. Finally, the advantages and the disadvantages of a CHP are explored.